Are behaviour and stress‐related phenotypes in urban birds adaptive?. Issue 8 (1st June 2022) - Caizergues, Aude E.; Grégoire, Arnaud; Choquet, Rémi; Perret, Samuel; Charmantier, Anne
Abstract: Urbanisation is a world‐wide phenomenon converting natural habitats into new artificial ones. Environmental conditions associated with urbanisation represent great challenges for wildlife. Behaviour and stress tolerance are considered of major importance in the adaptation to novel urban habitats and numerous studies already reported behavioural and stress response phenotypes associated with urbanisation, often suggesting they represented adaptations, while rarely demonstrating it. The main goal of this study was to test the adaptive nature of urban shifts in behavioural and stress‐related traits, and by adaptive we mean phenotypic change favouring traits in the same direction as selection. Using 7 years of monitoring of urban and forest great tits, we first tested for differences in exploratory behaviour, aggressiveness and breath rate, between both habitats. Second, we performed habitat‐specific analyses of selection on the three former traits using (a) reproductive success and (b) survival estimated via capture–mark–recapture models, as fitness estimates, to determine whether shifts in these behavioural and stress‐related traits were aligned with patterns of ongoing selection. We found that urban birds displayed higher exploratory behaviour and aggressiveness, and higher breath rate, compared to forest birds. Selection analyses overall revealed that these shifts were not adaptive and could even be maladaptive. In particular, higher handling aggression and higher breath rate in urban birds was associated with lower fitness. Higher exploration scores were correlated with lower survival in both habitats, but higher reproductive success only in forest males. Overall, differences in patterns of selection between habitats were not consistent with the phenotypic divergence observed. Taken together, these results highlight that phenotypic shifts observed in cities do not necessarily result from new selection pressures and could be maladaptive. We hypothesise that divergences in behavioural traits for urban birds could result from the filtering of individuals settling in cities. We thus encourage urban evolutionary scientists to further explore the adaptive potential of behavioural traits measured in urban habitats (a) by replicating this type of study in multiple cities and species, (b) by implementing studies focusing on immigrant phenotypes and (c) by measuring selection at multiple life stages. Abstract : City dwellers often present modified behaviour and stress‐related phenotypes compared to their rural counterparts. This research shows great tits in urban areas to be more aggressive, more exploratory and have higher breath rate. However, as these these shifts are not associated with higher fitness, it suggests they are not adaptations to urbanisation.